2010
DOI: 10.1021/op1001403
|View full text |Cite
|
Sign up to set email alerts
|

Organic Solvent Nanofiltration: A New Paradigm in Peptide Synthesis

Abstract: Solid-phase synthesis is the dominant paradigm for peptide synthesis, used ubiquitously from discovery to production scale. However, the solid-phase approach produces coupling steps that may not be quantitative, introducing errors in amino acid sequences. It also entails an excess of reagents to overcome mass transfer limitations and restrictions on solvent, coupling chemistry, and protecting groups. Organic solvent nanofiltration (OSN) is a newly emerging technology capable of molecular separations in organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 42 publications
0
45
0
Order By: Relevance
“…14 Membrane enhanced peptide synthesis (MEPS) improves the LPPS route by replacing extraction, precipitation, microfiltration and drying with diafiltration [15][16][17][18] , and has the advantage of significantly shorter processing time. 19,20 Previous studies have shown that this iterative approach can achieve high yield and purity for peptide, oligonucleotide and mono-disperse polyethylene glycol (PEG). [21][22][23] The following manuscript should be cited as: Wenqian Chen, Mahdi Sharifzadeh*, Nilay Shah, and Andrew G. Livingston.…”
Section: Introductionmentioning
confidence: 99%
“…14 Membrane enhanced peptide synthesis (MEPS) improves the LPPS route by replacing extraction, precipitation, microfiltration and drying with diafiltration [15][16][17][18] , and has the advantage of significantly shorter processing time. 19,20 Previous studies have shown that this iterative approach can achieve high yield and purity for peptide, oligonucleotide and mono-disperse polyethylene glycol (PEG). [21][22][23] The following manuscript should be cited as: Wenqian Chen, Mahdi Sharifzadeh*, Nilay Shah, and Andrew G. Livingston.…”
Section: Introductionmentioning
confidence: 99%
“…Solvent-resistant nanofiltration membranes with superior separation properties are also in high demand for the production of biopolymers and biodiesel [157,158]. In recent years, enormous quantities of oilcontaminated water have been produced in oil and gas fields, and the recycling of this water (so-called produced water) represents another important application for solvent-resistant filtration membranes.…”
Section: Ultrathin Porous Diamond-like Carbon Membranesmentioning
confidence: 99%
“…Thus SPOS requires a higher excess of the expensive monomers to drive coupling to completion than would be required in solution phase. Secondly, the intensity of SPOS is restricted by sub-maximal loading of the polymeric support to minimize interference between neighboring chains (particularly when preparing longer oligos), and thus maintain coupling efficiency 15 . Thirdly, the SPOS process is highly mass intensive at large scale 6 .…”
Section: Introductionmentioning
confidence: 99%